2003
DOI: 10.1021/jp0358578
|View full text |Cite
|
Sign up to set email alerts
|

Energetics and Electronic Structures of Individual Atoms Adsorbed on Carbon Nanotubes

Abstract: The adsorption of individual atoms on the semiconducting and metallic single-walled carbon nanotubes (SWNT) has been investigated by using the first principles pseudopotential plane wave method within density functional theory. The stable adsorption geometries and binding energies have been determined for a large number of foreign atoms ranging from alkali and simple metals to the transition metals and group IV elements. We have found that the character of the bonding and associated physical properties strongl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

20
87
1
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 121 publications
(110 citation statements)
references
References 33 publications
(75 reference statements)
20
87
1
1
Order By: Relevance
“…Ti is bound to ͑8,0͒ SWBNT surface with E b of 1.09 eV without facing energy barrier. This displays a lower binding energy than that is obtained for SWNT ͑2.2 eV͒, 35,36 but it is still strong. Among possible adsorption sites, the most energetic one is found to be near the hollow site, where Ti atom is slightly displaced toward B and N atoms.…”
Section: Absorption Of H 2 Molecule On Bare and Ti Covered (80) Scontrasting
confidence: 57%
“…Ti is bound to ͑8,0͒ SWBNT surface with E b of 1.09 eV without facing energy barrier. This displays a lower binding energy than that is obtained for SWNT ͑2.2 eV͒, 35,36 but it is still strong. Among possible adsorption sites, the most energetic one is found to be near the hollow site, where Ti atom is slightly displaced toward B and N atoms.…”
Section: Absorption Of H 2 Molecule On Bare and Ti Covered (80) Scontrasting
confidence: 57%
“…4,5 A comprehensive understanding of these forces at atomic and molecular level still remains a challenge. A great deal of computational 6,7 and experimental effort 3,5,7,8 has been devoted to elucidate these interactions. New techniques with improved sensitivities are needed to probe the dynamics of organic molecules on the surface of low-dimensional carbon nanomaterials.…”
mentioning
confidence: 99%
“…We found that the Ti atom favors the hexagonal site ͑above the center of the hexagon͒ and its binding energy was calculated to be 1.54 eV. Although the favorable adsorption site is the same for both ͑8,0͒ and ͑12,0͒ tubes, the binding energy of the latter ͑having larger radius, r = 4.7 Å͒ is approximately 0.6 eV smaller than that of the ͑8,0͒ tube 37,38 having r = 3.2 Å. This curvature effect is expected, since C 2p and Ti 3d hybridizations are enhanced at small radius.…”
Section: Single-wall Carbon Nanotubementioning
confidence: 84%